QUANTITATIVE AND MORPHOLOGICAL ASSESSMENT OF CHANGES IN HEMATOLOGICAL LABORATORY INDICATORS IN ACUTE MYELOBLASTIC LEUKEMIA - Nargiza Pulatova; Dilfuza Matkarimova (Web of Journals Publishing, 2024)
Aim of the study: To analyze the range of laboratory changes in patients with acute myeloblastic leukemia. Material and methods: The study was conducted with the participation of 103 patients with AML and 104 healthy donors without a history of cancer. The selection of patients was carried out when applying to the RSSPMCH from 2015 to 2023. The subjects' hematological blood parameters were analyzed on an automatic hematological analyzer "Sysmex" using test systems from the company "HUMAN, Germany".Results: Quantitative analysis of hematological parameters in groups of patients showed the presence of characteristic changes for acute leukemia, manifested by a significant decrease in hemoglobin content and the number of erythrocytes, as well as platelets, and an increase in the number of immature blast cells. This was accompanied by an increase in the median number of leukocytes, a decrease in the number of mature neutrophils with an acceleration of the ESR level. At the same time, quantitative and morphological analysis of the hematological parameters of the myelogram showed the presence of the main diagnostic indicator of acute leukemia - an increased number of blast cells of more than 30%. Carrying out cytochemical studies of blast cells made it possible to determine the variant of the disease, i.e. the presence of a positive reaction to myeloperoxidase and the detection of glycogen in the form of diffuse small granules are characteristic cytochemical signs of AML. At the same time, it is important to emphasize that more intense disturbances in bone marrow hematopoiesis and in peripheral blood were observed in the group of patients with a resistant course.
Keywords: acute myeloid leukemia, resistance, hematological parameters, laboratory abnormalities, myelogram, blasts.